2018
DOI: 10.3168/jds.2017-13360
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different treatments for early-lactation hyperketonemia on liver triglycerides, glycogen, and expression of key metabolic enzymes in dairy cattle

Abstract: Despite the widespread use of treatments for postpartum hyperketonemia in dairy cows, there is currently a lack of evidence comparing their effects on both the resolution of hyperketonemia and the potential effects on the liver of affected animals. The objective of our work was to investigate the effect of commonly used hyperketonemia treatments on hepatic triglyceride and glycogen content as well as on the mRNA and protein abundance of key enzymes involved in gluconeogenesis, ketogenesis, and lipid metabolism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
9
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 46 publications
2
9
1
1
Order By: Relevance
“…At milking time 28, the interaction of initial ketosis severity and ▶ Fig. 3 Development of various blood plasma parameters of cows with subclinical ketosis treatment with sodium propionate (SP), herbal extract (HE), or placebo (PL) orally administered 10 times (twice daily) from milking time 1 until milking time 10; concentrations of beta-hydroxybutyrate (BHB) (a), glucose (b), nonesterified fatty acids (NEFA) (c), GGT (d), and GLDH (e) are shown before treatment (milking time 0), 4 (milking time 14), and 18 (milking time 28) milking times after the end of the treatment for either KET-low (84 cows with initial cow-side blood-BHB ≥ 1.0 mmol/L and ≤ 1.2 mmol/L) or KET-high (39 cows with initial cow-side blood-BHB > 1.2 mmol/L) cows. Boxplots represent raw data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At milking time 28, the interaction of initial ketosis severity and ▶ Fig. 3 Development of various blood plasma parameters of cows with subclinical ketosis treatment with sodium propionate (SP), herbal extract (HE), or placebo (PL) orally administered 10 times (twice daily) from milking time 1 until milking time 10; concentrations of beta-hydroxybutyrate (BHB) (a), glucose (b), nonesterified fatty acids (NEFA) (c), GGT (d), and GLDH (e) are shown before treatment (milking time 0), 4 (milking time 14), and 18 (milking time 28) milking times after the end of the treatment for either KET-low (84 cows with initial cow-side blood-BHB ≥ 1.0 mmol/L and ≤ 1.2 mmol/L) or KET-high (39 cows with initial cow-side blood-BHB > 1.2 mmol/L) cows. Boxplots represent raw data.…”
Section: Discussionmentioning
confidence: 99%
“…The few studies available focused primarily on propylene glycol as medication, but only McArt et al described propylene glycol alone as subclinical ketotic treatment compared to placebo (PL) [11,12]. Propylene glycol was tested for treatment of subclinical ketosis in various combinations by adding niacin, insulin or butaphosphane-cyanocobalamin, glucocorticoids, glucose, or L-carnitine and methionine [13][14][15][16][17][18][19]. Glucose precursors like propylene glycol or sodium propionate (SP) were orally administered for 3 to 7 days as standard therapy in subclinical ketotic dairy cows in former studies (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Upregulation of this enzyme as it was predominantly observed in LP cows has been reported to occur in healthy dairy cows after calving [48]. ACC, an enzyme of the fatty acid biosynthesis catalyzing the conversion from acetyl CoA to malonyl-CoA was the only enzyme for which a weak but significant treatment effect was identified [49]. Slightly higher values in LP than in C cows are indicative of higher hepatic de-novo lipid synthesis in states of P-deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been repeatedly shown that liver glycogen concentration drastically decreases in early lactation (Weber et al, 2013(Weber et al, , 2015McCarthy et al, 2015), suggesting glycogenolysis. Recent manuscripts reporting hepatic concentrations of glycogen have aimed to evaluate the effects of different treatments or physiological conditions on liver glucose metabolism during the transition period and in early lactation (Hammon et al, 2009;Mann et al, 2018;Zenobi et al, 2018). Percutaneous needle liver biopsy was used in those studies, as it is the easiest way to obtain liver samples from live animals.…”
mentioning
confidence: 99%